2011
DOI: 10.5614/itbj.eng.sci.2011.43.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Various Orthodontic Retraction Springs

Abstract: Abstract. Retraction spring is a type of orthodontic apparatus that is used to move a tooth with respect to another by utilizing its spring back effect. It is made of metallic wire formed to individual orthodontic cases. A specific geometry results in a set of force system, consisting of forces and moments, that provides specific movement effect when it is pre-activated to the adjacent teeth. Currently, orthodontists select its geometry depending on their knowledge and experience. It is based on separate and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Analytical relations among spring characteristics, design, dimension, and activation distance in a given retraction loop must be considered to fully understand its biomechanical behavior (Setiawan et al). Several reports analyzed the effects of different wire crosssections, different pre-activation settings (symmetric arm activation vs. symmetric moments), and different IBD's on T-loops, either experimentally (Burstone;Manhartsberger et al, 1989;Kuhlberg & Burstone;Rose et al, 2009;Setiawan et al;Caldas et al, 2011aCaldas et al, , 2011b, or clinically (Martins et al;Keng et al, 2012;Xia et al, 2013;Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical relations among spring characteristics, design, dimension, and activation distance in a given retraction loop must be considered to fully understand its biomechanical behavior (Setiawan et al). Several reports analyzed the effects of different wire crosssections, different pre-activation settings (symmetric arm activation vs. symmetric moments), and different IBD's on T-loops, either experimentally (Burstone;Manhartsberger et al, 1989;Kuhlberg & Burstone;Rose et al, 2009;Setiawan et al;Caldas et al, 2011aCaldas et al, , 2011b, or clinically (Martins et al;Keng et al, 2012;Xia et al, 2013;Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With a correct selection of T-type loop, dental movement would be more accurate, minimizing treatment time and costs (Setiawan et al, 2011). Several studies have tried to modify the moment-toforce ratio (M/F) by changing either the position of the T-loop or its pre-activation bends, and have found that modifying loop height by applying a concave or convex bend in the upper portion of T-loops could affect the stiffness, force delivery and M/F ratio, due to the effect these vertical changes have in the resulting dental movement (Hoenigl et al, 1995;Kuhlberg & Burstone;Chen et al, 2000;Thiesen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the mean value, group B represented the highest value 0.313, while the lowest value was shown in group E 0.058 (Fig. [7][8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…appliances with implementation of active auxiliary springs can Volume 61 -June 2022 ISSN: 1110.435X be considered for orthodontic treatment [8].…”
Section: Removable Functionalmentioning
confidence: 99%